Development and Validation of a Three-Dimensional Printed Multifunctional Trap for Surveillance of Mosquitoes - Reinbold-Wasson, Drew David; Reiskind, Michael Hay (Journal of the American Mosquito Control Association, 2021)
An essential component of vector-borne disease monitoring programs is mosquito surveillance. Surveillance efforts employ various collection traps depending on mosquito species and targeted life-history stage, i.e., eggs, larvae, host-seeking, resting, or gravid adults. Surveillance activities often use commercial traps, sometimes modified to accept specific mosquito species attractants. The advent of widely available and affordable 3D printing technology allows the construction of novel trap designs and components. The study goal was to develop and assess a cost-effective, multipurpose, 6-volt mosquito trap integrating features of both host-seeking and gravid mosquito traps to collect undamaged live specimens: a multifunctional mosquito trap (MMT). We tested the MMT in comparison to commercial traps, targeting gravid Aedes albopictus , host-seeking Ae. albopictus , and total number of host-seeking mosquitos regardless of species. Field evaluations found the MMT performed as well as or better than comparable commercial traps. This project demonstrates an easy to construct, inexpensive, and versatile mosquito trap, potentially useful for surveying multiple mosquito species and other hematophagous insects by varying attractants into the MMT.